Geneza kanonu Pisma Świętego = The origins of the biblical canon - Królikowski, Janusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The contemporary biblical and theological studies draw special attention to shaping the biblical canon regarding the Old and the New Testament. This process is characterised by a lead?ing role of ?the rule of faith? (?the rule of truth?), which gradually became a major criterion used for the verification of Christian writings, making it possible to indicate those of them which can be considered as the foundation of faith and life of the Church.
Keywords: reguła wiary; reguła prawdy; ewangelie; kanon; Nowy Testament; apokryfy; "fragment Muratoriego"; rule of faith; rule of truth; Gospels; canon; New Testament; apocrypha; Muratorian fragment